Challenging but Connective: Large-Scale Characteristics of Synchronous Collaboration Across Time Zones - Mok, Lillio; Sun, Lu; Sen, Shilad; Sarrafzadeh, Bahar (CHI Conference on Human Factors in Computing Systems, 2023)
Organizations are becoming increasingly distributed and many need to collaborate synchronously over great geographical distances.Despite a rich body of literature on spatially-distanced meetings, gaps remain in our understanding of temporally-distanced meetings.Here, we characterize cross time zone collaborations by analyzing 20 million meetings scheduled at a multinational corporation,Micorosft, supported by a survey on how 130 employees perceive their scheduling needs. We find that cross time zone meetings areclosely associated with scheduling patterns around early morning and late evening hours, which are challenging and discordant withemployees’ stated temporal preferences. Additionally, the burdens of meeting across time boundaries are asymmetrically distributedamong workers at different levels of the organization and different geolocations. Nonetheless, we further observe evidence that crosstime zone attendees are organizationally distant and diverse, suggesting that addressing these challenges by limiting meetings woulddisafford employees the opportunities to connect. We conclude by sharing opportunities for facilitating cross time zone meetings thatfoster healthier global collaborations.